Pemberdayaan Kelompok Ibu-Ibu PKK dalam Program Penghijauan di Desa Motinelo Kecamatan Tabongo Kabupaten Gorontalo - Fatmah AR Umar; Wa Ode Irawati (Univeristas Negeri Gorontalo, 2022)
Reforestation is one of the important activities that must be implemented conceptually in dealing with the environmental crisis. This reforestation needs to be done through environmental education. Reforestation can be done if there is a will from each individual, for example the will of PKK women. This will will be the basis for implementing the reforestation program in Motinelo Village, Tabongo District, Gorontalo Regency. Departing from the description above, it is necessary to do community service, namely empowering PKK women in environmental greening activities in Motinelo Village, Tabongo District, Gorontalo Regency. Reforestation is very useful in overcoming various degradations in environmental quality by using the main material is the use of plants that are very functional in the biotic environment of the environment. The purpose of this service is to increase awareness of PKK women about the importance of carrying out environmental greening activities in order to maintain environmental quality and protection in the Motinelo Village, Tabongo District, Gorontalo Regency. This community empowerment activity aims to carry out reforestation activities through tree planting to improve environmental quality. In addition, this activity also aims to increase public awareness about environmental conservation. The environmental reforestation activity that will be carried out hopes that problems regarding the declining quality of the environment can be overcome by involving community participation. This is the essence of community empowerment, which can provide benefits to the community, especially PKK women in terms of environmental management. Another benefit that can be felt by the community is the increased awareness of PKK mothers on the importance of protecting the environment through reforestation.